T Cells in Adipose Tissue in Aging - Kalathookunnel Antony, Antu; Lian, Zeqin; Wu, Huaizhu (Frontiers in Immunology, 2018)
Similar to obesity, aging is associated with visceral adiposity and insulin resistance. Inflammation in adipose tissue, mainly evidenced by increased accumulation and proinflammatory polarization of T cells and macrophages, has been well documented in obesity and may contribute to the associated metabolic dysfunctions including insulin resistance. Studies show that increased inflammation, including inflammation in adipose tissue, also occurs in aging, so-called “inflamm-aging.” Aging-associated inflammation in adipose tissue has some similarities but also differences compared to obesity-related inflammation. In particular, conventional T cells are elevated in adipose tissue in both obesity and aging and have been implicated in metabolic functions in obesity. However, the changes and also possibly functions of regulatory T cells (Treg) in adipose tissue are different in aging and obesity. In this review, we will summarize recent advances in research on the changes of these immune cells in adipose tissue with aging and obesity and discuss their possible contributions to metabolism and the potential of these immune cells as novel therapeutic targets for prevention and treatment of metabolic diseases associated with aging or obesity.